ABOUT SELF-INDEPENDENT WORK OF STUDENTS AND ITS CONTROL AT TECHNICAL UNIVERSITY - N. A. Mikulik; A. A. Fedorov; M. A. Drozd (Наука и техника)
The paper considers students’ attitude to self-independent work and their usage of textbooks on the basis of questionnaires.